(untitled) (Eurasian Research Bulletin, 2023)
The most important nitrile used in industry is acrylonitrile. In the petrochemical and oil-producing industries, materials obtained on its basis are actively used. First of all, these are polyacrylonitrile fibers, acrylonitrile – butadiene – styrene resins and other plastic materials with such unique properties as high benzo, oil, frost resistance and others.